Running in Children and Adolescents with Cerebral Palsy - A Biomechanical Analysis and Intervention Study - Chappell, Annie (Curtin University, 2020)
This thesis investigated the effect of a task-specific, low-load plyometric running training program on the biomechanics of running in children and adolescents with CP in Gross Motor Function Classification Scale (GMFCS) Levels I and II. The thesis reports changes in running biomechanics following the intervention, specifically, improvements in ankle power generation for running in children in GMFCS Level II and improved leg stiffness in GMFCS Level I.